2017
DOI: 10.1080/03639045.2017.1349785
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of piribedil mucoadhesive tablets for efficient therapy of Parkinson’s disease: physical characterization andex vivodrug permeation through buccal mucosa

Abstract: Overall, HPMC was found to combine desired controlled release and mucoadhesion characteristics with sufficient pharmaceutical quality for optimization of buccal tablets. Piribedil mucoadhesive buccal tablets designed for the first time may introduce a new alternative for the treatment of Parkinson's disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…Buccal tablets were compressed by using a single-punch tablet machine (TDP-5; Shanghai Tianfan Machinery Factory, Shanghai, China) equipped with 7-mm round flat punch set. 20 Tablet weight was kept constant at 100 mg, and the thickness of tablets was adjusted tô2 mm. Tablets were stored in an airtight container away from the light for further studies.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Buccal tablets were compressed by using a single-punch tablet machine (TDP-5; Shanghai Tianfan Machinery Factory, Shanghai, China) equipped with 7-mm round flat punch set. 20 Tablet weight was kept constant at 100 mg, and the thickness of tablets was adjusted tô2 mm. Tablets were stored in an airtight container away from the light for further studies.…”
Section: Methodsmentioning
confidence: 99%
“…Mucoadhesive strength of tablets was determined by using a texture analyzer (Middleboro, MA, USA). 20 , 26 Fresh buccal mucosa from the sheep obtained from local slaughterhouse was used as a model membrane. Samples were prepared by separating the underlying adipose tissue, and the obtained mucosal membrane was cut into 2×2 cm pieces.…”
Section: Methodsmentioning
confidence: 99%
“…HEC is frequently used in the formulation of gels with mucous administration because it was demonstrated to be similar to the fertile cervical mucus [ 24 , 25 ]. On the other hand, HPMC is used as excipient in more than 80% of the pharmaceutical products with oral administration [ 26 ] and, unlike HEC, has the property of retaining water, structuring the gel in a particular manner without dehydrating the biological substrate when it gets in contact with [ 27 , 28 ], thus providing comfort feel in occlusive state of application. The flexibility and the elasticity of the polymeric films are ensured by plasticizers (e.g., polyethylene glycol, propylene glycol and polysorbates) which often can also act as permeation activators, when they breach into the corneous layer of the epidermis [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ].…”
Section: Introductionmentioning
confidence: 99%
“…Piribedil was estimated in formulations by Yardimci et al using micellar electrokinetic capillary chromatography [10] . In addition to these analytical methods, few other research articles reported enhancement of dissolution pattern of piribedil [11] , optimization of piribedil mucoadhesive tablets [12] , characterization of piribedil buccal tablets [13] and in vivo evaluation of piribedil solid lipid micro and nanoparticles [14] . No method has so far been reported for the estimation of impurities in piribedil prolonged release tablets.…”
mentioning
confidence: 99%